Dental Negligence: Accidental Administration of Formalin Instead of Local Anesthetic - Manohar, B.; Ranjitha, R. S.; Bhuvaneshwari, S.; Awasthi, R.; Humagain, M. (Kathmandu University Medical Journal, 2021)
A solution like formalin used as a fixative has to be handled with lot of care and needs to be stored with utmost care. Negligence on part of the dental professional by accidentally injecting formalin instead of the local anesthetic can lead to permanent tissue damage and also may induce a life threatening situation. The operating dentist injected formalin accidentally instead of the local anesthetic and the patient experienced severe pain and burning sensation. The general practice of formalin being stored in the local anesthetic bottles and being assisted by untrained assistant is the most common reason for mishaps to happen. The dentist operating should be careful and aware of the drugs and chemicals being available in the operatory and re-check the solution being injected in the patient as to not land up in complications because of the negligence.